Family and provider perceptions of quality of care in the management of sick young infants in primary healthcare settings in four counties of Kenya. Issue 3 (7th July 2021) - Mbugua, Samuel; Gitaka, Jesse; Gitau, Tabither; Odwe, George; Mwaura, Peter; Liambila, Wilson; Ndwiga, Charity; K'Oduol, Kezia; Warren, Charlotte; Abuya, Timothy
Abstract : Background: Understanding the perceptions of quality of care given to sick young infants in primary healthcare settings is key for developing strategies for effective uptake and utilisation of possible severe bacterial infection guidelines. The purpose of this study is to assess families and providers' perceptions of care given to sick young infants at primary healthcare facilities in four diverse counties in Kenya. Methods: A cross-sectional qualitative design involving 37 in-depth interviews and 39 focus group discussions with very young (15–18 years), young (19–24 years) and older (25–45 years) caregivers of young infants aged 0–59 days; and key informant interviews with community-based and facility-based front-line health providers (14) in primary healthcare facilities. Qualitative data were captured using audio tapes and field notes, transcribed, translated and exported into QSR NVivo V.12 for analysis. A thematic framework approach was adopted to classify and analyse data. Results: Perceived care given to sick young infants was described around six domains of the WHO framework for the quality of maternal and newborn healthcare: evidence-based practices for routine and emergency care; functional referral systems; effective communication; respect and preservation of dignity; availability of competent, motivated human resources; and availability of physical resources. Views of caregivers and providers regarding sick young infant care in primary healthcare settings were similar across the four sites. Main hindrance to sick young infant care includes stockout of essential drugs, limited infrastructure, lack of functional referral system, inadequate providers which led to delays in receiving treatment, inadequate provider skills and poor provider attitudes. Despite these challenges, motivation and teamwork of health providers were key tenets in care provision. Conclusion: The findings underscore the need to prioritise improving quality of sick young infant services at primary healthcare settings by building capacity of providers through training, ensuring continuous supply of essential medicines and equipment and improving infrastructure including referral.